Ekspresi dan Aktivasi Sub Unit p65 NF-κB pada Sel Mononuklear Penderita Sindrom Nefrotik Resisten Steroid Anak - Corebima, Brigitta Ida RV; Subandiyah, Krisni; Fitri, Loeki Enggar (Jurnal Kedokteran Brawijaya, 2009)
Resitance  to  steroid  therapy  is  a  poor  prognosis  sign  for  nephrotic  syndrome,  but  this  mechanism is  still unclear. NF-κB has been reported to affect the glucocorticoid at the T cell through the transrepression in  the glucocorticoid  receptor .  Until  know,  this  study  was  still  limited.  The  aim  of  this  study  was  to  show  the  difference expression  and  activation  of  NF-κB  p65  subunit  between  childhood  SRNS  and  SSNS  patient.  Cross  sectional study  was  conducted  during  January  2009  to  December  2009  in  the  Saiful Anwar  General  Hospital  and Biomedic  Laboratory  Brawijaya  University.  Expression  and  activation  of  NF-κB  p65  subunit  were  determine  by immunochemistry  staining  by  counting  the  amount  of  lymphocyte  that  express  and  activate  NF-κB  p65  subunit among  200  lymphocytes  under  light  microscope  with  1000  magnification.  Results  was  analyzed  by independent  t  test  with  95%  CI  (p<0,05)  and  Pearson  correlation.  The  result  of  this  study  revealed  no significant  difference  of  expression  of  NF-κB p65  subunit  between  SRNS and  SSNS  (p=0,153),  but  there  was an increase activation of NF-κB p65 subunit in the SRNS patients (p=0,000).